A two-stage modelling approach for the analysis of the stress distribution in anchorage zones of pre-tensioned, concrete elements. (15th July 2017) - Steensels, R.; Vandewalle, L.; Vandoren, B.; Degée, H.
Highlights: A two-stage modelling approach for anchorage zones of prestressed concrete is presented. Stage 1 computes an appropriate bond-slip model and transfer length. Stage 2 analyses the anchorage zone with nonlinear concrete material behaviour. Numerical results of both stages are validated with experimental data. Abstract: An innovative strategy for the analysis and design of the anchorage zones of pre-tensioned, concrete girders is presented. In this approach, the bond behaviour of the prestress strands is first characterised in a small-sized beam model. A new relation between the slip and radial strain of the prestress strand is introduced and used together with the radial stress–strain relation resulting from a thick-walled cylinder model to establish the bond-slip behaviour at the steel–concrete interface. This bond behaviour is implemented in a numerical model and validated via a comparison of the computed transfer length with the results of two experimental campaigns. Next, the bond-slip relation of the small-scale model is applied in full-scale models of pre-tensioned, concrete girders to derive the stress distribution in the anchorage zones. The non-linear material behaviour of concrete is taken into account and a comparison of the numerical results with full-scale experimental data is made. An acceptable agreement is achieved between the experimental results and the numerical calculations regarding the bond behaviour and transfer lengths as well as the crack patterns and the stress values in the reinforcement bars. This efficient modelling approach allows for a full analysis of the anchorage zone based solely on the geometrical and material properties known at the design stage.